The refusal of maternity in the struggle between corset and the reproductive function (Revista de Ensino em Artes, Moda e Design, 2022)
The present work follows on the master’s research of the author and aims to investigate, through the studies of Elizabeth Badinter (1985), the relations between breastfeeding and the moralistic criticism directed to the use of stays and corsets, which mainly took place in France, England and Germany urban regions from 18th and 19th centuries. The qualitative research with bibliographic and museum sources demonstrates that the State's concerns with the maintenance and increase of human capital impacted the way such garments were perceived. The changes occurred in the shape and structure of stays and corsets are, therefore, witnesses of the process responsible for incorporating the practices of motherhood within the notion of femininity.
Keywords: stays; corsets; motherhood; reproductive function